Digital Mediatization and the Sharpening of Malaysian Political Contests - Yin, Pauline Pooi (ISEAS - Yusof Ishak Institute, 2021)
The introduction of the Multimedia Super Corridor in 1996 was due to the Malaysian government's initiative to tap into the ICT sector. While this move spearheaded Malaysia into the knowledge economy, digital media enabled the opposition and civil society to compete and break the government's monopoly over information flows.Digital mediatization of politics in Malaysia encouraged cyberattacks such as DDoS attacks, hacking and spamming. Cyberbullying on social media is also on the rise.